DOES A DIGITAL STORY TELLING (DST) AFFECT STUDENTS' SPEAKING ABILITY ON RECOUNT? : AN EXPERIMENTAL STUDY - musdalifah musdalifah (Language-Edu, 2020)
Speaking is a kind of skills in a language component that used for communication. It is important for students to be mastered. Students get difficult to use a language. Moreover, they have to express their idea in English. The teacher must be considered to make an interesting and use a good approach to teach them in the class. Teaching speaking should be related in using a technology. Furthermore, in this era of 21st Century. Teachers should be able to attract the students’ attention by using a computer program or a smartphone in teaching learning process. Digital Story Telling (DST) provide teachers and students to express an idea of telling a story by using a computer program. Recount is a kind of text that can be told by the students in DST. They can tell about their own experience trough DST in teaching learning process.